Análise das interações entre as principais commodities minerais brasileiras - Ramser, Claudia Aline de Souza (2016)
In the current market, the commodities trading directly influences the economy of a country. These goods are on the trade balance, which is made up by imports and exports of a country. This study aims to determine the relationship between mineral commodities in order to understand, identify and quantify their impact on the Brazilian economy in the short and long-term relationship, through autorregresssive vectors models. Uses is a VAR modeling in mineral commodities such as oil, coal and crude oil and determines its effects and interrelations. In a second step we use the PC-VAR estimation to determine the impact of other mineral commodities on oil, coal and crude. In Chg unrestricted oil was the most important variable and is estimate the PC-VAR, which afforded reduce the number of variables in study, it was observed that the CP had the same behavior with the original variables. Thus it was possible to quantify the contribution of each variable when the shock occurs, and the time that such shock will act in the equations, as well as their interactions.